Effects of growth regulators on development of soybean (Glycine max cv. Davis) - Castro, Paulo R.C.; Moraes, Roberto S. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1980)
This study was conducted with the objetive of determining the effects of growth regulators on soybean plant (Glycine max) under greenhouse conditions. Plants 21 days after sowing were sprayed with (2-chloroethyl) trimethyl ammonium chloride (CCC) 2,000 ppm, succinic acid-2,2-dimethylhydrazide (SADH) 4,000 ppm, giberellic acid (GA) 100 ppm, indolylacetic acid (IAA) 100 ppm, and water as a check treatment. GA increased plant height while SADH and CCC showed a reduction for this trait. On the other hand, CCC and SADH treatments showed an increasing trend for total number of leaves. Number of leaves in the main stem was increased with GA, and number of leaves in secondary stems was increased with SADH. Diameter of soybean stem was increased with CCC.